DOKTRIN NASIONALISME DALAM NOVEL A. HASJMY - Wildan, Wildan (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2010)
This study discusses nationalism that has been portrayed in seven novels written by A. Hasjmy, an Acehnese writer. The novels are Melalui Jalan Raya Dunia (1938), Bermandi Cahaya Bulan (1939), Suara Azan dan Lonceng Gereja (1940), Nona Pressroom (1951), Elly Gadis Nica (1951), Meurah Djohan: Sultan Aceh Pertama (1976), and Tanah Merah: Digul Bumi Pahlawan Kemerdekaan Indonesia (1976). The aim of the study is to analyze doctrine of nationalism in the context of Indonesian politics. The main finding of this study shows that Indonesian nationalism is obviously well represented in the novels. This finding is contrary to the public opinion that most of the Acehnese are supporters of the separatist movement, i.e. Acehnese nationalism. Thus, in portraying the nationalism, A. Hasjmy has exploited certain writing techniques in his novels, such as epistolary, speeches, diary, poems and footnotes to camouflage its doctrines and missions. With these findings, the significance of this study is it could elucidate academically that not every Acehnese agrees with the idea of Aceh separatism.